The impact of vascular factors on language localization in the superior temporal sulcus. Issue 8 (22nd January 2014) - Wilson, Stephen M.
Abstract The left superior temporal sulcus (STS) has been shown in numerous functional imaging studies to be a critical region for language processing, as it is reliably activated when language comprehension is compared with acoustically matched control conditions. Studies in non‐human primates have demonstrated several subdivisions in the STS, yet the precise region(s) within the STS that are important for language remain unclear, in large part because the presence of draining veins in the sulcus makes it difficult to determine whether neural activity is localized to the dorsal or ventral bank of the sulcus. We used functional MRI to localize language regions, and then acquired several additional sequences in order to account for the impact of vascular factors. A breath‐holding task was used to induce hypercapnia in order to normalize voxel‐wise differences in blood oxygen level‐dependent (BOLD) responsivity, and veins were identified on susceptibility‐weighted and T2*‐weighted BOLD images, and masked out. We found that the precise locations of language areas in individual participants were strongly influenced by vascular factors, but that these vascular effects could be ameliorated by hypercapnic normalization and vein masking. After these corrections were applied, the majority of regions activated by language processing were localized to the dorsal bank of the STS. Hum Brain Mapp 35:4049–4063, 2014. © 2014 Wiley Periodicals, Inc.